Optimization of computer ontologies for e-courses in information and communication technologies - Sabitova, Nazym; Tikhonov, Yuriy; Lakhno, Valerii; Kariyrbek, Makulov; Kryvoruchko, Olena; Chubaievskyi, Vitalyi; Desiatko, Alona; Zhumadilova, Mereke (International Journal of Electronics and Telecommunications, 2024)
A methodology is proposed for modifying computer ontologies (CO) for electronic courses (EC) in the field of information and communication technologies (ICT) for universities, schools, extracurricular institutions, as well as for the professional retraining of specialists. The methodology includes the modification of CO by representing the formal ontograph of CO in the form of a graph and using techniques for working with the graph to find optimal paths on the graph using applied software (SW). A genetic algorithm (GA) is involved in the search for the optimal CO. This will lead to the division of the ontograph into branches and the ability to calculate the best trajectory in a certain sense through the EC educational material, taking into account the syllabus. An example is considered for the ICT course syllabus in terms of a specific topic covering the design and use of databases. It is concluded that for the full implementation of this methodology, a tool is needed that automates this procedure for developing EC and/or electronic textbooks. An algorithm and a prototype of software tools are also proposed, integrating machine methods of working with CO and graphs.